Será possível prevenir a alergia alimentar? - Carrapatoso, I (2007)
The rising prevalence of food allergy has led to particular interest in intervention studies designed to prevent its onset. These studies have been performed on high-risk children in particular. Primary intervention studies are difficult to perform due to the complexity of design and selection of patients. Analyses and comparison of the results of different studies are exceedingly difficult to interpret owing to differences in selection criteria, primary outcomes and methods used to confirm the diagnosis of allergy. In spite of these limitations, there are several prospective, randomised, blind studies that have demonstrated the benefits of food allergy prevention. In these studies dietary intervention in the first 4 to 6 months promoted a decrease in infantile atopic eczema and cow¿s milk allergy. While some dietary restrictions are recommended for all infants, particular measures should be applied to high risk children. The aim of this study was to review the literature on primary prevention of food allergy focusing on breast and formula feeding, maternal diet in pregnancy and while breast-feeding, age of solid food introduction and probiotics.